1D p–n Junction Electronic and Optoelectronic Devices from Transition Metal Dichalcogenide Lateral Heterostructures Grown by One‐Pot Chemical Vapor Deposition Synthesis. (4th May 2021) - Najafidehaghani, Emad; Gan, Ziyang; George, Antony; Lehnert, Tibor; Ngo, Gia Quyet; Neumann, Christof; Bucher, Tobias; Staude, Isabelle; Kaiser, David; Vogl, Tobias; Hübner, Uwe; Kaiser, Ute; et al.
Abstract: Lateral heterostructures of dissimilar monolayer transition metal dichalcogenides provide great opportunities to build 1D in‐plane p–n junctions for sub‐nanometer thin low‐power electronic, optoelectronic, optical, and sensing devices. Electronic and optoelectronic applications of such p–n junction devices fabricated using a scalable one‐pot chemical vapor deposition process yielding MoSe2 ‐WSe2 lateral heterostructures are reported here. The growth of the monolayer lateral heterostructures is achieved by in situ controlling the partial pressures of the oxide precursors by a two‐step heating protocol. The grown lateral heterostructures are characterized structurally and optically using optical microscopy, Raman spectroscopy/microscopy, and photoluminescence spectroscopy/microscopy. High‐resolution transmission electron microscopy further confirms the high‐quality 1D boundary between MoSe2 and WSe2 in the lateral heterostructure. p–n junction devices are fabricated from these lateral heterostructures and their applicability as rectifiers, solar cells, self‐powered photovoltaic photodetectors, ambipolar transistors, and electroluminescent light emitters are demonstrated. Abstract : Monolayer MoSe2 ‐WSe2 lateral heterostructures with atomically precise 1D boundaries are synthesized using a one‐pot chemical vapor deposition process. Their functional properties are demonstrated in various electronic, optoelectronic, photovoltaic, and light‐emitting devices.